Kajian Pengembangan Pengisian Data Hujan yang Hilang dengan Data CHIRPS di Wilayah Bali - Arsanti Aphrodita, Nerisa Fedria; Yuliara, I Made; Yuda, I Wayan Andi (Universitas Hamzanwadi, 2023)
Research has been carried out related to the study of filling in missing rain data with CHIRPS data in the Bali Region. This study aims to determine the validation of daily and monthly CHIRPS rain data with observational data in the Bali region and to know the results of filling in observation rain data with corrected CHIRPS data. There are also differences in patterns between CHIRPS data and observational data that require data correction that was carried out using simple regression. This study shows that corrected CHIRPS shows RMSE and MBE valueshave lower error rates than CHIRPS without correction. As an example, the results of the calculation of data accuracy are shown by the RMSE and MBE values after being corrected which are better than CHIRPS before being corrected. For Sukasada rain post, the RMSE values before and after correction are 15.355 mm and 13.527 mm for daily data and 77.586 mm and 65.083 mm for monthly data, respectively. Meanwhile, the MBE values for the Sukasada rain post before and after correction were -0.875 mm and -0.017 mm for daily data and -27.142 mm and 0.005 mm for monthly data, respectively